Imbalance of Tumor Suppression Genes Expression Following Rat Tongue Carcinogenesis Induced by 4-Nitroquinoline 1-Oxide - Ribeiro, Daniel Araki (2009)
This study was undertaken to investigate, by immunohistochemistry, the expression of some tumor suppressor genes such asp 16, p21 and Retinoblastoma (Rb) during 4-Nitroquinoline I-oxide induced rat tongue carcinogenesis. Male Wistar rats were distributed into three groups of 10 animals each and treated with 50 ppm 4NQO solution through their drinking water for 4, 12 or 20 weeks. Ten animals were used as negative control. Neither histopathological abnormalities were induced in the epithelium after 4 weeks of carcinogen exposure, not-statistically significant differences (p>0.05) in expression of all the tumor suppressor genes were found when compared to the negative control. However, the levels of Rb were increased (p<0.05) in pre-neoplastic lesions at 12 weeks following carcinogen exposure. In well-differentiated squamous cell carcinoma induced after 20 weeks of treatment with 4NQO, p16 and Rb were expressed in some tumor cells. Taken together, the results support the belief that the expression of Rb is closely event-related to malignant transformation and conversion of the oral mucosa, being a reliable biomarker linked to oral cancer pathogenesis.